2022
DOI: 10.1371/journal.pone.0262262
|View full text |Cite
|
Sign up to set email alerts
|

SPATS2 is positively activated by long noncoding RNA SNHG5 via regulating DNMT3a expression to promote hepatocellular carcinoma progression

Abstract: Hepatocellular carcinoma (HCC) is one of the most prevalent malignant tumors with high mortality worldwide. Spermatogenesis-associated serine-rich 2 (SPATS2) could be a novel diagnostic and prognostic biomarker in HCC. However, the regulatory mechanism of SPATS2 in HCC requires further elucidation. Therefore, the study’s objective was to investigate this process in HCC. In this study, we found that SPATS2 is significantly upregulated in HepG2 cells to promote cell growth and migration. SPATS2 is the target tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Li et al discovered that SNHG5 contributed to the proliferation and migration of hepatocellular carcinoma (HCC) cells through regulating GSK3β and the Wnt/β-catenin signalling pathway by competitively binding miR-26a-5p [ 33 ]. Yan et al suggested that SNHG5 could promote the proliferation and migration of HCC cells by upregulating spermatogenesis-associated serine-rich 2 ( SPATS2) expression ( 47 ). Zhang et al indicated that SNHG5 accelerates the proliferation, migration and invasion of cervical cancer cells through upregulating sex-determining region Y-Box 4 ( SOX4 ) expression via competitive sponging of miR-132 [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al discovered that SNHG5 contributed to the proliferation and migration of hepatocellular carcinoma (HCC) cells through regulating GSK3β and the Wnt/β-catenin signalling pathway by competitively binding miR-26a-5p [ 33 ]. Yan et al suggested that SNHG5 could promote the proliferation and migration of HCC cells by upregulating spermatogenesis-associated serine-rich 2 ( SPATS2) expression ( 47 ). Zhang et al indicated that SNHG5 accelerates the proliferation, migration and invasion of cervical cancer cells through upregulating sex-determining region Y-Box 4 ( SOX4 ) expression via competitive sponging of miR-132 [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Several lncRNAs have been identified to serve as the prognostic indicators for HCC, such as TUG1, [12] LINC01234, [11] and SNHG5. [14] Recently, homeobox transcript antisense intergenic RNA (HOTAIR), a lncRNA, has been verified to be associated with the prognosis of HCC. [13,[15][16][17][18][19][20][21][22] Han et al study showed high HOTAIR expression was an independent prognostic factor of overall survival (OS) (P < .01) and progression-free survival (PFS) (P < .01) in patients with advanced HCC treated by sunitinib.…”
Section: Introductionmentioning
confidence: 99%